1991
DOI: 10.3109/00016349109007162
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme (β‐D‐N‐acetylglucosaminidase) released from the decidua to maternal plasma prior to the onset of labor

Abstract: Changes in the activity of beta-N-acetylglucosaminidase (E.C. 3.2.1.30; NAG), a lysosomal marker enzyme, in the maternal plasma and utero-placental tissues during late pregnancy and parturition were examined in order to determine if lysosomal enzymes participate in the cervical ripening. NAG activity in the plasma gradually increased as gestation advanced, to reach a maximum 3-4 days before the spontaneous onset of labor, and remaining at this level until the second stage. The activity measured in decidua and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…NAG was released to the maternal circulation mainly from the decidua and only partly from the amnion. Lysosomal enzyme release occurs prior to the onset of labor, it may play a role primarily in the ripening of the cervix [27]Previous studies have shown that NGAL participated in a variety of biochemical processes involving embryonic development and cell differentiation, this may be the reason why there were signi cant differences between pregnant women and non-pregnant women. there was no variation of serum NGAL values through the whole pregnancy and is consistent with the study by D'Anna R, [20] During the late pregnancy, the sensitivity of osmoceptor to antidiuretic hormone dropped This change may be mediated by increased β-human chorionic gonadotropin, a pattern also seen to a lesser degree in menstruating women during the luteal cycle[28]and then led to retention of sodium and water and further caused GFR rose ,which increased with the raised blood volume and renal blood ow (RBF); so the excretion of urea nitrogen and creatinine would increase and then the level of urea nitrogen and creatinine in serum would decrease, it's accordance with ndings in this report that a signi cant decrease in BUN, Cr.…”
Section: Discussionmentioning
confidence: 99%
“…NAG was released to the maternal circulation mainly from the decidua and only partly from the amnion. Lysosomal enzyme release occurs prior to the onset of labor, it may play a role primarily in the ripening of the cervix [27]Previous studies have shown that NGAL participated in a variety of biochemical processes involving embryonic development and cell differentiation, this may be the reason why there were signi cant differences between pregnant women and non-pregnant women. there was no variation of serum NGAL values through the whole pregnancy and is consistent with the study by D'Anna R, [20] During the late pregnancy, the sensitivity of osmoceptor to antidiuretic hormone dropped This change may be mediated by increased β-human chorionic gonadotropin, a pattern also seen to a lesser degree in menstruating women during the luteal cycle[28]and then led to retention of sodium and water and further caused GFR rose ,which increased with the raised blood volume and renal blood ow (RBF); so the excretion of urea nitrogen and creatinine would increase and then the level of urea nitrogen and creatinine in serum would decrease, it's accordance with ndings in this report that a signi cant decrease in BUN, Cr.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Nagase in uterine fluid may be important for implantation and may play a role as an initiator of its adhesive phase (Boving 1963). The experiments describing Nagase activity during human parturition revealed that the enzyme may be involved in cervical ripening (Takenaka et al 1991). The enzyme may also alter glycosaminoglycan metabolism, change cell permeability or affect cell‐cell interactions and show luteal involvement (Hansen et al 1984).…”
Section: Discussionmentioning
confidence: 99%